Imaging of oesophageal cancer with FDG-PET/CT and MRI. Issue 1 (January 2015) - van Rossum, P.S.N.; van Lier, A.L.H.M.W.; Lips, I.M.; Meijer, G.J.; Reerink, O.; van Vulpen, M.; Lam, M.G.E.H.; van Hillegersberg, R.; Ruurda, J.P.
<x xml:space="preserve">Abstract</x> Integrated 2-[18F]-fluoro-2-deoxy-d-glucose (FDG) PET/CT and magnetic resonance imaging (MRI) with functional features of diffusion-weighted imaging (DWI) are advancing imaging technologies that have current and future potential to overcome important limitations of conventional staging methods in the management of patients with oesophageal cancer. PET/CT has emerged as an important part of the standard work-up of patients with oesophageal cancer. Besides its important ability to detect unsuspected metastatic disease, PET/CT may be useful in the assessment of treatment response, radiation treatment planning, and detection of recurrent disease. In addition, high-resolution T2-weighted MRI and DWI have potential complementary roles. Recent improvements in MRI protocols and techniques have resulted in better imaging quality with the potential to bring improvement in staging, radiation treatment planning, and the assessment of treatment response. Optimal use and understanding of PET/CT and MRI in oesophageal cancer will contribute to the impact of these advancing technologies in tailoring treatment to the individual patient and achieving best possible outcomes. In this article, we graphically outline the current and potential future roles of PET/CT and MRI in the multidisciplinary management of oesophageal cancer.